On the development of textual competence in primary education - Cardoso, Adriana; Pereira, Susana; Silva, Encarnação; Sousa, Otília (L1-Educational Studies in Language and Literature, 2009)
The aim of this article is to present the results of an action research project, which has been put into practice in Primary Education. This project was intended to develop students' textual competence, considering both comprehension and textual production. Our starting hypothesis was that teaching the schematisation of text types, focusing on linguistic devices that underlie text production, would promote the development of textual competence, leading to the production of more coherent and cohesive texts. In order to test this hypothesis we implemented the project in three phases. First, before the intervention, we collected texts produced by the students. Secondly, we implemented a didactic program designed to develop students' textual competence. Lastly, after the intervention, we collected students' texts once again. Data was analyzed according to categories that confer cohesion and coherence to different types of texts. Narrative, descriptive, and explanatory texts were assessed in terms of 1) building an autonomous text; 2) hierarchisation of information, and 3) textual organisation. Overall, results indicate that students developed their text conceptualisations, their understanding of the different structures of texts, and produced better writing. Indeed, their written work shows a marked progression from the beginnin of the intervention program to the end of the program.